CONCENTRATION OF SOME HEAVY METALS RESULTING FROM THE INCINERATION OF WIND-BORNE MEDICAL WASTE IN AL-QASIM GENERAL HOSPITAL (British Journal of Global Ecology and Sustainable Development, 2022)
This research included the environmental assessment of the heavy metals obtained from the work of the incinerator in Al-Qasim General  Hospital.  Through this study, heavy elements generated from internal and external medical wastes from the incinerator were examined by four observations in the morning and evening during the study period, where some elements were measured, their quantities were determined and compared with the permissible determinants, where the results obtained from the chemical and physical examinations showed that there is a large discrepancy from one sample to another, and it is almost non-existent in some samples.  Al-Qasim General Hospital achieves some high efficiency rate in the burning process, according to the staff working in that hospital.